USM VC RECEIVES DELEGATION FROM CAMBODIA - MPRC, Pusat Media & Perhubungan Awam (USM, 2017)
USM, PENANG, 10 April 2017 – The Universiti Sains Malaysia (USM) ViceChancellor, Professor Datuk Dr. Asma Ismail received a courtesy visit from the Cambodia Fellowship Monitoring delegation, led by the Deputy DirectorGeneral of Higher Education Cambodia, Dr. Nith Bunlay, today.